The declaratory judgment - Woolf, Harry; Woolf, Jeremy; Mackay, Ronald D.; Zamir, Itzhak (Litigation library, 2011)
This book explains the purpose and remit of this important remedy and goes through statute and case law to illustrate when a declaratory judgment can be granted. It highlights the advantages of using declaratory proceedings, shows how to bring a case before the court, and explains the jurisdiction of the High Court, county courts and tribunals to grant declarations. Detailed examination of who is entitled to bring proceedings for declaratory relief - both claimant and defendant - is included, together with a comparative study of the use of the declaratory process in Scotland